Impacto de los medios de comunicación televisivos digitales en el desarrollo profesional post - pandemia en el cantón Quevedo, Provincia de Los Ríos, año 2021 - Murillo Mohina, Jamil Alexander (2021)
This project will be based on demonstrating how the media have evolved with the advancement of technology in the 21st century and how it has been developed and in such a way to be able to demonstrate the reality experienced because of the new strain called Virus Covid 19 that It has hit many countries in their economy, politics and health, which Ecuador was not obsolete to that. The role of the media is considered the most important from immemorial times to the present; since it helps to be able to inform and transmit facts based from the most important to the most obsolete. In the city of Quevedo, the issue of digital media has been progressed and implemented in an ascending way, which has helped to reach several homes in the aforementioned canton, with important information for this community.